Power Representation and Public Resistance in the Hashtag Discourse #BubarkanDPR: A Critical Discourse Analysis - Muhamad Saiful Mukminin; Ahmad Abdul Muhhit; Libra Dui Putra; Jefri Zolila; Md. Kamruzzaman Khandoker; Aqeel Ahmed (Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The development of social media in Indonesia has created a digital public space that enables people to express aspirations, criticism, and protest. One prominent phenomenon is hashtag activism, such as #BubarkanDPR. This study aimed to analyze the representation of power and public resistance in the digital discourse of #BubarkanDPR. The research combined qualitative and quantitative methods, employing descriptive and interpretative approaches to understand language patterns, symbolism, and public resistance strategies, as well as frequency analysis of words, hashtags, and lexicons to identify dominant patterns and the intensity of public expression. The data consisted of 1,237 posts on the X platform using the hashtag #BubarkanDPR from August 20 to September 1, 2025, collected through crawling using Python and tweet-harvest Node.js, and then manually cleaned. The analysis was conducted using Norman Fairclough’s AWK model of Critical Discourse Analysis (CDA), covering text analysis, discourse practice, and socio-cultural practice, with the assistance of AntConc 4.3.1 to map wordlists, word frequencies, collocations, and KWIC. The findings revealed that the DPR was represented as a symbol of corruption, betrayal, and democratic failure, while the public expressed resistance through delegitimization, collective calls, and emotional and vulgar language. These results underscore an ideological shift toward anti-establishment sentiments and highlight the role of digital democracy as a battleground for power.